2023
DOI: 10.2989/10220119.2022.2138973
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the breakdown in the indigenous knowledge system for rangeland management and policy: a case study from the Eastern Cape in South Africa

Abstract: Communal rangelands inSouth Africa are generally perceived as overgrazed owing to complexities in their histories and collective utilisation which often leads to improper management. A suitable solution has not been found in land management policies because local people's contexts and their indigenous knowledge are ignored. Hence, this paper is aimed at (i) assessing the role indigenous knowledge can play in communal rangeland management, (ii) exploring working solutions to incorporate indigenous knowledge int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…These studies point out the opportunities to adapt herd composition and management to changes in vegetation and soil condition and to use this information to inform restoration and livestock nutrition. Finca et al (2023) reported a case study, which found that communal farmers from the Eastern Cape in South Africa have in-depth indigenous and spatial knowledge about the management and changes in condition of their rangelands. However, because of ageing communal farmers, limited youth participation, and declines in agricultural extension services, this knowledge is increasingly not being incorporated to ensure effective communal rangeland management.…”
Section: Guest Editorial African Rangelands and Pastoralism In A Chan...mentioning
confidence: 99%
See 2 more Smart Citations
“…These studies point out the opportunities to adapt herd composition and management to changes in vegetation and soil condition and to use this information to inform restoration and livestock nutrition. Finca et al (2023) reported a case study, which found that communal farmers from the Eastern Cape in South Africa have in-depth indigenous and spatial knowledge about the management and changes in condition of their rangelands. However, because of ageing communal farmers, limited youth participation, and declines in agricultural extension services, this knowledge is increasingly not being incorporated to ensure effective communal rangeland management.…”
Section: Guest Editorial African Rangelands and Pastoralism In A Chan...mentioning
confidence: 99%
“…Both these studies outline that there is great value in indigenous knowledge and opportunities exist to use this knowledge to improve rangeland and livestock farming. Finca et al (2023) highlight the opportunity for agricultural extension to assist with the knowledge flow amongst communal farmers and aid in the generational transfer of indigenous knowledge. Both these two studies embrace the use of new technologies and modern science that farmers can either incorporate into their indigenous knowledge and training or to identify the potential forages for cattle feeding in free-range beef farming.…”
Section: Pastoralists' Indigenous Knowledgementioning
confidence: 99%
See 1 more Smart Citation